If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6r + -9s + 5t) * 3 = 0 Reorder the terms for easier multiplication: 3(6r + -9s + 5t) = 0 (6r * 3 + -9s * 3 + 5t * 3) = 0 (18r + -27s + 15t) = 0 Solving 18r + -27s + 15t = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '27s' to each side of the equation. 18r + -27s + 27s + 15t = 0 + 27s Combine like terms: -27s + 27s = 0 18r + 0 + 15t = 0 + 27s 18r + 15t = 0 + 27s Remove the zero: 18r + 15t = 27s Add '-15t' to each side of the equation. 18r + 15t + -15t = 27s + -15t Combine like terms: 15t + -15t = 0 18r + 0 = 27s + -15t 18r = 27s + -15t Divide each side by '18'. r = 1.5s + -0.8333333333t Simplifying r = 1.5s + -0.8333333333t
| 2y/3-5/12=y/4 | | 4x+7=15+2x | | 5x-20=70/14 | | 2/3-2x-3x=3/4-5x-16 | | -83=3(8x+4)+1 | | 2/3-2x-3x | | Ln(x)=290.25 | | ln(x)=290.95 | | 2/3-5x=-61/4-5x | | w^2+20w+16=0 | | 5x+6=11x | | -2+x=6x-17 | | 4[9-3(8m+1)]-8m= | | F(x)=9xln(3x)-9x | | 6+8x=5x+9 | | 4ln(x+2)+3ln(4x+9)= | | 4[2(x-3)]= | | 7y+y(6-8)= | | 3x+x=1.35 | | 40-n=4n+7 | | 3x+x=135 | | 7(x-1)=6x+1 | | X^2-13x+60=90 | | 88=2+2(8-5x) | | 8x+6=5x+5 | | g-4=-3 | | 22=x^2 | | (-x^5/2)^4 | | m-9=3 | | y=1.2+0.8(-2) | | ln(x)+ln(5x)=9 | | -89=x+75 |